Giant Prepyloric Ulcer Haemorrhage: Patient Characteristics, Treatment, and Outcome in 2003–2012. (10th April 2014) - Peetsalu, Margot; Kirsimägi, Ülle; Peetsalu, Ants
Abstract : The aim of the study was to characterize patients with giant prepyloric ulcer haemorrhage, their treatment, and outcome. The data for 929 peptic ulcer haemorrhage (PUH) patients were divided into three groups according to ulcer location: group I: 165 prepyloric ulcer patients, group II: 353 gastric ulcer patients, and group III: 411 duodenal ulcer patients. Among these groups giant ulcer (ulcer diameter ≥ 2 cm) haemorrhage cases were selected for the study and the data for group I were compared with the data for groups II and III. The study shows that the proportion of giant ulcers in all prepyloric ulcers was significantly 2.2 times lower compared with the proportion of giant ulcers in all gastric ulcers and 1.5 times lower than the proportion of giant ulcers in all duodenal ulcers. The share of surgical therapy for haemorrhages from giant prepyloric ulcers did not differ from the share of surgical therapy in the case of giant gastric ulcers but was 3.5 times lower than in the case of giant duodenal ulcers. Generally, treatment for PUH from giant prepyloric ulcers was successful not involving inhospital mortality.